Case Reports of Severe Congenital Neutropenia Treated With Unrelated Cord Blood Transplantation With Reduced-intensity Conditioning. Issue 1 (January 2016) - Osone, Shinya; Imamura, Toshihiko; Fukushima-Nakase, Yoko; Kitamura-Masaki, Ayaka; Kanai, Sotaro; Imai, Tomohiko; Imashuku, Shinsaku; Kuroda, Hiroshi
Abstract : Allogeneic stem cell transplantation is a curative treatment for severe congenital neutropenia (SCN). However, a standard conditioning regimen and donor source have not been established. We report 3 consecutive cases of SCN who were successfully treated by cord blood transplantation (CBT) with reduced-intensity conditioning consisting of fludarabine, melphalan, and low-dose total body irradiation. All cases achieved complete donor chimerism without severe infectious complications and have maintained normal neutrophil counts for between 3 and 9 years after CBT. These results suggest that CBT with reduced-intensity conditioning can be an alternative therapy for SCN when human leukocyte antigen-matched bone marrow donor is unavailable.